A Tale of Two Twins. (11th September 2019) - Sayers, Judy
Abstract : This is the ninth year the Biochemical Society has run the Science Communication Competition . The competition aims to give talented young science communicators the opportunity to have their work published in The Biochemist . This year's competition attracted entries from around the world covering a wide variety of topics, in both the written and video categories. The entries were judged by our expert panel of judges. In this issue we are proud to present the winning entry from the written category by Judy Sayers from the University of Cambridge.